Therapeutic hypothermia in asphyxiated neonates, using phase change material (Mira Cradle): experience from neonatal intensive care unit of tertiary care centre South India - Dr. Devina Saraswat; Gayathri Aradhya; Chaitali R.; G. Guruprasad (Pediatric Review: International Journal of Pediatric Research, 2020)
Introduction: Therapeutic hypothermia (TH) is now recommended for the treatment of neonates with Hypoxic-Ischemic Encephalopathy(HIE).This treatment protocol is applied in our department since June 2016. The aim of this study is to report our experience with whole body cooling in asphyxiated neonates admitted in a level 3, Bapuji NICU, Davangere.Patients and Methods: Prospective study of newborns admitted for HIE from July 2017 to July 2018 that is one year, in Neonatal Intensive Care Unit (NICU) of BCHI, Davangere. The results were reported as short term and long-term neurodevelopment assessment at 1-year age on a newborn group who received hypothermia.Results: Seventy-two cases of neonates with perinatal asphyxia were admitted in the unit. According to inclusion criteria 50 cases were eligible for the study. The arrival beyond six hours of life was the main cause accounting for not starting therapeutic cooling in birth asphyxia cases. Short come outcome measured in terms of requirement of anticonvulsants, cardiovascular instability, need of mechanical ventilation during stay was significantly reduced with therapeutic cooling. Long term outcome in term of neurodevelopment assessment at 1-year age found significant improvement overall in all domains.Conclusion: Our first experience with the controlled TH supports its beneficial effect in newborns with HIE. This treatment must be available in all the centers involved in the neonatal care.